Assessment of performance of steel and GFRP bars as injected anchors in masonry walls. (1st October 2016) - Ceroni, Francesca; Cuzzilla, Roberto; Pecce, Marisa
Highlights: Experimental pull-out tests on steel and GFRP bars as injected anchors in masonry walls. Effect of bar diameter and type, grout type on the bond behaviour and strength. Comparison with several literature and code provisions for different failure modes. Parametric analysis for assessing injected anchors reliability under seismic actions. Abstract: The first part of the paper presents the results of two series of in situ pull-out tests of injected anchors embedded in existing yellow tuff masonry walls. Anchors are made of steel and GFRP bars with diameter of 12 and 20 mm and were embedded by means of two types of grout: a cement-based and a pozzolana-based grout. The results were examined in terms of both maximum load and displacement to determine the most efficient bar-grout coupling. The experimental pull-out forces are also compared with the predictions given by several literature formulas. The second part of the paper is devoted to verify the efficiency of the tested injected anchor systems for avoiding out-of-plane damage mechanisms in masonry walls having varying slenderness and subjected to horizontal forces; to this aim parametric analyses were performed to calculate the seismic acceleration required to activate several out-of-plane mechanisms and to verify the effectiveness of injected anchors similar to those experimentally tested into avoiding them.